(untitled) (Brazilian Journal of Radiation Sciences, 2021)
The Fukushima Daiichi nuclear accident in Japan in 2011 has raised public fears about the actual safety of nuclear power plants in several countries. The response to this concern by government agencies and private companies has been objective and pragmatic in order to guarantee best practices in the several phases of nuclear reactors. In countries where the nucleo-electric matrix is consolidated, such as the United States, France and the United Kingdom, the safety assessment is carried out considering deterministic and probabilistic criteria. In the licensing stages of new projects, it is necessary to analyze and simulate the behavior of the nuclear power plant, when subjected to conditions that can lead to sequences of accidents. Probabilistic Safety Assessment (PSA) is fundamental in this process, as it studies in depth the sequences of events that can lead to damage to the reactor core. Such sequences should be quantified in terms of probability of occurrence and your possible consequences, and organized through techniques such as Fault Tree Analysis and Event Tree Analysis. The present work will describe the procedures for the realization of PSA and its applicability to the assurance of the operational reliability of the nuclear reactors, as well as a brief comparative between the approaches used in some countries traditionally users of thermonuclear energy and Brazil. By means of this analysis, it can be concluded that nuclear power is increasingly reliable and safe, being able to provide the necessary tranquility for the population of the countries where it is inserted.